2016
DOI: 10.4103/0022-3859.183167
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of microscopy and rapid diagnostic tests in malaria diagnosis in areas with varying parasite density among older children and adult patients in Nigeria

Abstract: Background:Current malaria control strategies are based on early diagnosis and appropriate treatment of malaria cases. The study aimed at comparing the performance of blood film microscopy and rapid diagnostic test (RDT) in Plasmodium falciparum detection in patients ≥6 years of age.Materials and Methods:A total of 154 consecutive pyretic patients aged 6-62 years were enrolled, sampled, and tested for malaria using RDT (first response) and microscopy by Giemsa staining. Genomic DNA was extracted after saponin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…In the same vein, World Health Organization has observed that most prevalent malaria parasite species in sub Saharan Africa was P. falciparum (WHO, 2003). Indeed, the high malaria parasite prevalence recorded in this study was also similar to the reports of previous studies in other parts of Nigeria (Greenwood et al, 2005;Asaolu & Igbaakin, 2009;Okonko et al, 2009;Iwueze et al, 2014;Ayogu et al, 2016;Umma et al, 2017;Awosolu et al, 2019Awosolu et al, , 2020. However, malaria parasite prevalence in this study is greater than studies reported by Nzeako et al (2013), Udoh et al (2013) and Simon-Oke et al (2019).…”
Section: Discussionsupporting
confidence: 91%
“…In the same vein, World Health Organization has observed that most prevalent malaria parasite species in sub Saharan Africa was P. falciparum (WHO, 2003). Indeed, the high malaria parasite prevalence recorded in this study was also similar to the reports of previous studies in other parts of Nigeria (Greenwood et al, 2005;Asaolu & Igbaakin, 2009;Okonko et al, 2009;Iwueze et al, 2014;Ayogu et al, 2016;Umma et al, 2017;Awosolu et al, 2019Awosolu et al, , 2020. However, malaria parasite prevalence in this study is greater than studies reported by Nzeako et al (2013), Udoh et al (2013) and Simon-Oke et al (2019).…”
Section: Discussionsupporting
confidence: 91%
“…The overall malaria prevalence in this study using Giemsa microscopy as the gold standard was 43.1%. The study prevalence is comparable to 46.6% reported in Zamfara State [ 15 ], 40.8% in Rivers State [ 16 ], and 40.5% in South-Eastern Nigeria [ 17 ] but lower than 72.5% in Rivers State [ 18 ], 85.7% in Enugu State [ 19 ], and 71.4% in Cross River State [ 20 ]. The study prevalence (43.1%) is higher than 15.0% in Ogun State [ 21 ] and 14.7% in Lagos [ 22 ].…”
Section: Discussionsupporting
confidence: 78%
“…The performance of RDTs (aldolase) in malaria diagnosis in this study is in agreement with previous studies conducted, showing that RDTs performed better than microscopy in malaria diagnosis under field conditions [21,[30][31][32][33]. The performance of pLDH was well below optimum in sensitivity.…”
Section: Sensitivity and Specificity Of Diagnostic Techniquessupporting
confidence: 91%